Pengembangan Olahan Ikan Kembung untuk Mencegah Stunting di Desa Tedunan Wedung Demak - Yudanti, Gendis Purno; Palupi, Dian Arsanti; Handayani, Yanulia; Ismah, Kadar; Setyoningsih, Heni (Muria Jurnal Layanan Masyarakat, 2023)
Stunting is a chronic nutritional problem if it isn't controlled with catch-up growth it will cause decreased growth, increases the death risk and inhibits motor and mental growth. The Indonesian Government promise to reduce the prevalence of stunting so it needs to strengthen coordination and expand the scope of programs carried out by related Government Institutions. Tedunan, one of the villages on the coast of Demak which becomes the target of reducing stunting rates, it has abundant marine products but has not been used optimally. Based on Journal of Nutrition and Food Science 2016, an important ingredient found in mackerel is selenium. Selenium plays a role in reducing the risk of low birth weight and the risk of stunting. This community service program aims to increase consumption of mackerel by making nuggets which are ready to eat and are liked by children and increase the economic selling value of mackerel.